2019
DOI: 10.1186/s12879-019-4130-0
|View full text |Cite
|
Sign up to set email alerts
|

Potential circulating biomarkers of circulating chemokines CCL5, MIP-1β and HA as for early detection of cirrhosis related to chronic HBV (hepatitis B virus) infection

Abstract: Background Due to no clinical symptoms in the compensated stage of cirrhosis, it is usually diagnosed when decompensated complications occur. In this study, the noninvasive circulating biomarkers for early detection to compensated stage of cirrhosis in patients with chronic HBV (hepatitis B virus) infection was explored. Methods According to the Guideline of Prevention and Treatment of Chronic Hepatitis B (2015 Update), 78 patients with CHB (chronic hepatitis B) were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…In a previous study, Hu et al found that CCL5 is a reliable biomarker for predicting liver fibrosis and cirrhosis: the expression of CCL5 in serum and hepatic tissue first increased in CHB patients with ongoing liver injury and then significantly decreased in advanced liver cirrhosis patients. 20 Moreover, CCL5 and its receptor CCR5 have been established with roles in cancer progression and tumour immune evasion mechanisms, including in HCC. 21 , 22 An antagonist of CCL5 was found to ameliorate liver fibrosis and prevent HCC in mouse models, which further strengthened the relationship between CCL5 and liver fibrosis or carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study, Hu et al found that CCL5 is a reliable biomarker for predicting liver fibrosis and cirrhosis: the expression of CCL5 in serum and hepatic tissue first increased in CHB patients with ongoing liver injury and then significantly decreased in advanced liver cirrhosis patients. 20 Moreover, CCL5 and its receptor CCR5 have been established with roles in cancer progression and tumour immune evasion mechanisms, including in HCC. 21 , 22 An antagonist of CCL5 was found to ameliorate liver fibrosis and prevent HCC in mouse models, which further strengthened the relationship between CCL5 and liver fibrosis or carcinogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…This is primarily due to factors such as delay in or absence of diagnosis 6 8 . Candidates for liver cancer are commonly patients with underlying liver diseases, such as hepatitis B virus (HBV) infection and cirrhosis 9 . More than half of sick HCC persons are diagnosed with advanced disease, restricting treatment options.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, we found that CD74, CCL5, CXCL10 and PTPRC were the 4 common genes in terms of the gene co-expression network. The serum level of CCL5 is a reliable marker that can predict disease progression in chronic hepatitis B patients [51]. The intrahepatic expression of CXCL10 was significantly increased in the HBeAg (+) compared to the HBeAg (−) patients [52].…”
Section: Discussionmentioning
confidence: 99%